Intermediate Algebra (12th Edition)

Published by Pearson
ISBN 10: 0321969359
ISBN 13: 978-0-32196-935-4

Chapter 4 - Section 4.4 - Multiplying Polynomials - 4.4 Exercises - Page 304: 38



Work Step by Step

We are given the expression $(4x-1)(6x-7)$. We can find the product of this expression using the FOIL method. First terms: $4x\times 6x=24x^{2}$ Outer terms: $4x\times-7=-28x$ Inner terms: $-1\times 6x=-6x$ Last terms: $-1\times-7=7$ Adding together: $24x^{2}+(-28x)+(-6x)+7=24x^{2}-28x-6x+7=24x^{2}-34x+7$
Update this answer!

You can help us out by revising, improving and updating this answer.

Update this answer

After you claim an answer you’ll have 24 hours to send in a draft. An editor will review the submission and either publish your submission or provide feedback.